Misconceptions and Behavioral Risks in Parental Antibiotic Use on Romanian Children: A Cross-Sectional Study on Knowledge, Attitudes, and Practices - Alin Iuhas; Radu Galiș; Marius Rus; Andreea Balmoș; Cristian Marinău; Larisa Niulaș; Zsolt Futaki; Dorina Matioc; Cristian Sava (Antibiotics)
Background: Antimicrobial resistance is a growing global health threat, with antibiotic misuse in pediatric populations being a significant contributing factor. In Romania, antibiotic consumption and resistance rates are among the highest in Europe. Objective: To assess Romanian parents’ knowledge, attitudes, and practices regarding antibiotic use in children, and to identify key misconceptions and behavioral risks contributing to inappropriate antibiotic use. Methods: A cross-sectional survey was conducted among 400 parents of hospitalized children in a pediatric department in Romania. Participants completed a 15 item structured questionnaire. Data were analyzed using descriptive statistics, chi-square tests, and binary logistic regression to examine associations and control for potential confounding effects between education level, residential environment, and parental misconceptions regarding antibiotic use. Results: Among the 400 surveyed caregivers, 86% (n = 344) held at least one misconception regarding antibiotic use. Additionally, 42.5% (n = 170) of participants reported that they had never heard of the concept of antibiotic resistance. Misconceptions were significantly more prevalent among individuals with lower levels of education and those residing in rural areas (p < 0.001). While 89.8% (n = 359) stated that they had never administered antibiotics to their children without a physician’s recommendation, a separate subset of 28% (n = 112) acknowledged that they had asked a doctor to prescribe antibiotics for their child. Moreover, 23.3% (n = 93) reported seeking a second medical opinion when antibiotics were not initially prescribed. Conclusions: Despite high adherence to medical advice, widespread misconceptions persist. These findings highlight the need for targeted, population-specific educational interventions to promote rational antibiotic use and address AMR in high-burden settings like Romania.